Traumatic Skepticism of COVID 19 (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The impact of the Coronavirus Disease (COVID-19) is not just limited to fatalities around the world in the present times. The psychosocial impact is catastrophic and will last much longer than ever anticipated. The stigma attached to the fear of an isolated and lonely death, the trauma of not being close to your loved ones, the societal economic derailment, the loss of campus experiences by freshmen at any level across the globe, and above all the mass hysteria of staying caged behind closed doors until all is well demands the restructuring of both the physical and psychological aspects of the society. Even the stress and pressure on the medics and scientists across the globe is immense. The lurking fear of uncertainty, the pain of losing jobs, livelihood, businesses, and homes along with exposure to contradicting information has taken its toll on people’s peace of mind. The masses are struggling to adapt to the new world in the hope that everything will go back to the usual ‘normal’ soon. Only long-lasting and effective measures for physical and mental well-being, astute direction, and the planned steps can help heal the trauma of skeptical life ahead.